Learning from Excellence to Improve Healthcare Services: The Experience of the Maternal and Child Care Pathway - Alice Borghini (International Journal of Environmental Research and Public Health, 2021)
The ability to deal with adversity and the resilience of people and groups are shown to depend positively on the tendency to nurture positivity. Therefore, the aim of this study is to evaluate whether Learning from Excellence (LfE) can be an effective method to manage systematic health systems, when transparent disclosure and benchmarking of data are adopted in performance evaluation. This study consists of a quantitative and a qualitative phase. In the former, maternal care is investigated at the regional level, starting from performance data and indicators of the maternity pathway referred to 98 healthcare providers in 10 Italian regions, that share the same evaluation system. The second phase investigates qualitatively the organizational determinants and the experience of professionals involved in the pathway, through the organization of on-site workshops. We identified the seven best practices among the 42 units of analysis. Communication, trust and shared goals among health professionals involved in the pathway emerged as core themes from the qualitative analysis. This study confirms that LfE under the conditions of benchmarking assessment and transparent disclosure of data can be implemented systematically in management practice, in order to boost health personnel’s resilience and, in general, the organizational climate in the working environment.